Strengthening Policy Networks to Create Effective Public Policies - Rizky Ilhami (International Publisher (YAPENBI), 2023)
Quality public policy is an important factor in achieving sustainable development goals and community welfare. However, many public policies currently face challenges in their implementation due to a lack of coordination and synergy between the various parties involved in the policy formulation process. This research aims to investigate the role and importance of strengthening policy networks in the process of formulating effective public policies. Through a qualitative approach, data will be collected through in-depth interviews and analysis of relevant policy documents. This research will also analyze various case studies of public policy scenarios at various levels of government and sectors. The research results show that policy networks play an important role in an inclusive and responsive policy formulation process. By involving various actors and interest groups, policy networks are able to create broader consensus, increase policy legitimacy, and produce more informed decisions. Through close collaboration between government, the private sector and civil society organizations, policy networks can respond to complex issues with more holistic solutions, while ensuring transparency, accountability and a balanced distribution of power. Thus, strengthening policy networks as a whole is the key to creating effective and sustainable public policies.